Effects of Medical Hand Washing on Hand Flora among Staff Nurses - Kabita Dhami; Padmapriya S; Sasi Kumar S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: One of the leading causes of hospital associated infection is providing patient care withcontaminated hands as a result of transmission of microorganism from health care provider to patientsand others. Hand washing is the most important and simple act of reducing the spread of transmission ofinfectious agent and reducing hand flora. Materials and Methods: The study was done to evaluate theeffects of medical hand washing on hand flora among staff nurses working in a selected hospital, Bengaluru.One group time series design was used. Swabs were taken from a randomly selected sample of 25 nursesworking in medical ward for hand flora analysis. Results: Study results revealed that before hand washingthere were many colonies of hand flora were found. After medical hand washing there was a significantreduction in the number of colonies of the hand floras between the pre-test mean (O1= 10.02) and post-testsmean (O2= 4.23, O3 = 4.02 and O4 = 2.36) and was found to be statistically significant at H= 83.288 andP value = 0.001. Conclusion: Medical hand washing is an effective technique to reducing the hand floraamong the staff nurses working in the different medical wards of hospital.